Crosslinguistic research in syntax and semantics : negation, tense, and clausal architecture - Zanuttini, Raffaella (Georgetown University round table on languages and linguistics series (2004), 2006)
"This book contains truly fundamental contributions concerning the functional makeup of the sentence by some of the very best specialists around the world."?Guglielmo Cinque, Dipartimento di Scienze del Linguaggio, Universita' Ca' Foscari Venezia, Ital.